Corticomedullary Mixed Tumor of the Adrenal Gland with Apparent F-18-Fluorodeoxyglucose Activity But No 68GA-DOTATATE Uptake on Positron Emission Tomography/Computed Tomography - ENGÜR, CEREN ÖZGE; APAYDIN, TUĞÇE; ÖNEŞ, TUNÇ; ÖZGÜVEN, SALİH (My University, 2022)
Corticomedullary mixed tumor (CMT) is a single adrenal tumor mass composed histologically by an admixture of adrenal cortical and medullary cells. It is a rare condition, with approximately 20 cases reported to date. To our knowledge, the positron emission tomography (PET) imaging findings of this mostly benign tumor have not been reported in the literature. We present a case of CMT who was evaluated with both F-18-fluorodeoxyglucose (F-18-FDG) and Ga-68-DOTATATE. The hypermetabolic tumor seen on F-18-FDG PET/computed tomography scan showed no abnormal uptake by Ga-68-DOTATATE.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Klinik Tıp; Klinik Tıp (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; CLINICAL MEDICINE; Clinical Medicine (MED); Radyoloji ve Ultrason Teknolojisi; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiological and Ultrasound Technology; Radiology, Nuclear Medicine and Imaging; F-18-fluorodeoxyglucose positron emission tomography/computed tomography; Ga-68-DOTATATE positron emission tomography/computed tomography; adrenal gland; corticomedullary mixed tumor; 8F‑fluorodeoxyglucose positron emission tomography/computed tomography; 68Ga‑DOTATATE positron emission tomography/computed tomography; adrenal gland; corticomedullary mixed tumor